Mutations inside rifampicin-resistance determining region of rpoB gene associated with rifampicin-resistance in Mycobacterium tuberculosis - Myo T. Zaw; Nor A. Emran; Zaw Lin (Elsevier, 2018)
Background: Rifampicin (RIF) plays a pivotal role in the treatment of tuberculosis due to its bactericidal effects. Because the action of RIF is on rpoB gene encoding RNA polymerase β subunit, 95% of RIF resistant mutations are present in rpoB gene. The majority of the mutations in rpoB gene are found within an 81 bp RIF-resistance determining region (RRDR). Methodology: Literatures on RIF resistant mutations published between 2010 and 2016 were thoroughly reviewed. Results: The most commonly mutated codons in RRDR of rpoB gene are 531, 526 and 516. The possibilities of absence of mutation in RRDR of rpoB gene in MDR-TB isolates in few studies was due to existence of other rare rpoB mutations outside RRDR or different mechanism of rifampicin resistance. Conclusion: Molecular methods which can identify extensive mutations associated with multiple anti-tuberculous drugs are in urgent need so that the research on drug resistant mutations should be extended. Keywords: Mutations, Rifampicin-resistance determining region, rpoB gene, Rifampicin resistance, Mycobacterium tuberculosis